Depression in postmenopause: interdisciplinary approach in management and perspectives for rehabilitation - D. V. Blinov; E. S. Akarachkova; D. M. Ampilogova; E. M. Dzhobava; V. I. Tsibizova; A. G. Solopova; N. V. Pavlova; D. I. Korabelnikov; D. A. Petrenko (IRBIS LLC, 2022)
Surgical and natural menopause is often associated with depression symptoms. Along with the postpartum period, perimenopause is a "window of vulnerability" for depression development, because decline in estrogen level accounts for extinction of reproductive function, emotional disorders, genitourinary menopausal syndrome, which are combined with non-endocrine risk factors, such as decreasing income levels, low social support, and stress. Although a direct relationship between blood estrogens level and depression has not been demonstrated, the relation between menopause symptoms and depression has been proven, i.e., the symptoms of menopause can be considered as risk factors. Here, we summarizes the current view on the correct counseling and routing of menopausal women with depression symptoms in primary health care facilities, the principles of managing patients with risk factors, including genitourinary menopausal syndrome, as well as methods of rehabilitation and informational support. This will aid to improve the quality of medical care for such patients.